Main Policies Affecting Corporate Performance of Agri-Food Companies Vietnam - Junaid, M. Shaikh; Dinh Thi, Bao Linh (2017)
Vietnam is now one of the leading producers and exporters of important agricultural commodities, which has helped the country to have more influence in food security and trade of the region. In addition to its success in production and export, Vietnam also attracts investors and business around the world by its legal framework reform. In addition to a review on corporate performance of agri-food companies in Vietnam, an analysis of legal framework and policies affecting corporate performance of agri-food companies in Vietnam will provide a panorama on the business environment in the process of economic integration and trade liberalization.. However in the coming times, more policies adjustment and measures should be taken in order to encourage the sustainable development of agri-food companies. Along with the economic integration and trade liberalization, Vietnam is opening its market with 100 million consumers and also business opportunities to international business and investors. Is the stock market a transparent and efficient channel for their choice? That depends not only on the legal framework, but also on the performance of Vietnamese companies that may become their partners or rivals. Key words: Policies, Corporate Performance, Agriculture, Vietnam